2019
DOI: 10.37236/7970
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Graphs into a Spanning Tree, an Even Graph, and a Star Forest

Abstract: We prove that every connected graph can be edge-decomposed into a spanning tree, an even graph, and a star forest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the same year it was also proved to hold for claw-free (sub)cubic graphs by Aboomahigir, Ahanjideh, and Akbari [9] as well as by Hong et al [10]. More recently, Lyngsie and Merker [11] showed that weakening the matching requirement to allow for paths of length 2 suffices to make the conjecture true and Heinrich [12] verified it for 3-connected cubic graphs of tree-width 3. Earlier this year, Xie, Zhou, and Zhou [13] proved the conjecture for graphs with a two-factor consisting of three cycles.…”
Section: Introductionmentioning
confidence: 94%
“…In the same year it was also proved to hold for claw-free (sub)cubic graphs by Aboomahigir, Ahanjideh, and Akbari [9] as well as by Hong et al [10]. More recently, Lyngsie and Merker [11] showed that weakening the matching requirement to allow for paths of length 2 suffices to make the conjecture true and Heinrich [12] verified it for 3-connected cubic graphs of tree-width 3. Earlier this year, Xie, Zhou, and Zhou [13] proved the conjecture for graphs with a two-factor consisting of three cycles.…”
Section: Introductionmentioning
confidence: 94%
“…In the same year it was also proved to hold for claw-free (sub)cubic graphs by Aboomahigir, Ahanjideh, and Akbari [8]. More recently, Lyngsie and Merker [9] showed that weakening the matching requirement to allow for paths of length 2 suffices to make the conjecture true and Heinrich [10] proved the conjecture for 3-connected cubic graphs of tree-width 3. Earlier this year, Xie, Zhou, and Zhou [11] proved its validity when the graph has a two-factor consisting of three cycles.…”
Section: Introductionmentioning
confidence: 99%